A Study On Socio-Economic And Educational Status Of Tea Garden Labourers With Special Reference To Powai Tea Estate, Tinsukia, Assam (Journal of Namibian Studies : History Politics Culture, 2022)
Assam is one of the largest producers of tea in India.Tea industry of Assam has been providing acrucial contribution for the economic growth of the nation. The tea garden labourer plays veryimportantrole for the growth and development of the tea-estates of Assam.Tea communityforms a greater segment of Assamese society. They came to Assam for the purpose of tea industry during the time of British East India Company. The tea garden labourers always work hard for the better existence of tea industry but due to some hidden factors their socio-economic condition is not developed. The present paper discussed about various aspects of tea garden labourers of Assam with special reference to Powai tea-Estate and it examined about the main causes of their socio-economic and educational condition, exploitation in society based on the primary data of field survey and other secondary sources.The paper tried to find out various solution to improve the socio-economic and educational status of tea garden people.Because, equal opportunity and equal distribution of resources among every section of society is always necessary to establish a welfare and developed nation. Tea community as one of the most crucial part of Assam, their all-round development is always very necessary to strengthen democracy.